Sexual history evidence and the rape trial - Conaghan, Joanne (Bristol University Press, 2023)
"The use of a rape victim's sexual history as evidence attracted intense public attention after the acquittal of footballer Ched Evans in 2017. Set within the context of a criminal justice system widely perceived to be failing rape victims, the use of sexual history evidence remains a flashpoint of contention around rape law reform. This accessible book mounts an important interrogation into the use of a victim's sexual history as evidence in rape trials. Adopting a critical multidisciplinary perspective underpinned by feminist theory, the authors explore the role and significance of sexual history evidence in criminal justice responses to rape"--